Development of Non-Clinical Performance Indicators in Hospitals: Focusing on Stress Management and Medical Staff Burnout - Dewi Agustina; Nadia Maimunah Tarihoran; Cindy Aulia Pratiwi; Rizkya Salsabila Simanjuntak; Rahma Fadhila; Nabila Zahrah; Zaskia Nabilla; Defani Zasqiyah Putri; Ami Manda Atika Putri; Elma Riska Dwiana; Mawadah Karunia Br Ginting; Indrila Sembiring (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Hospital performance is determined not only by clinical indicators, but also by non-clinical factors that reflect the well-being and mental health of medical staff. In recent years, the increase in cases of work stress and burnout among healthcare workers has become a serious issue that directly impacts service quality, patient safety, and organizational sustainability. Therefore, this study is important to examine and develop non-clinical performance indicators that focus on managing stress and burnout among medical staff. This study uses a literature review approach to various relevant national and international studies. The results of the review show that integrating psychological well-being aspects into the hospital performance appraisal system can improve organizational effectiveness and create a healthy and productive work environment. Thus, the development of non-clinical indicators based on staff well-being is a strategic step in strengthening the hospital performance management system in the modern era.